Sistema web de gestión de citas e historias clínicas para el centro odontológico especializado Disan Cuñumbuqui - San Martín 2023 - Mosquera Pérez, Junior Marco (2024)
The DISAN specialized dental center located in the district of Cuñumbuqui in the province of Lamas in the San Martín region, at the initiative of the management in the face of the loss of patients and the lack of adequate care in consultations, the question arose: how Will the implementation of a web system contribute to the management of appointments and registration of medical records? The objective was to determine the contribution of this system and an improvement in management was expected. The study was quantitative, applied, with non-experimental intervention, analytical, longitudinal and prospective. The longitudinal trend design was used to explain the aforementioned contribution. The sample universe was made up of 830 patients, 364 came from May 1 to 28 and 466 came from June 5 to 30, 2023. To determine the difference between before and after implementation regarding the management of appointments and history records clinics, Chi square for homogeneity was used and to determine whether patient satisfaction improved, Mann-Whitney U was used with a significance level of 5%. Regarding appointment management, it improved from 89.9% to 100%; Regarding the management of medical records, it improved from 79.4% to 100%; and satisfaction improved from disagreeing to completely agreeing. It is concluded that the implementation of a web system improves the management of appointments and registration of medical records.